Pure gauge QCD and holography - Trinchero, Roberto Carlos (2014)
Holographic models for the pure gauge quantum chromodynamics (QCD) vacuum are explored. The holographic renormalization of these models is considered as required by a phenomenological approach that takes the β-functions of the models as the only input. This approach is done taking the dilaton as the coordinate orthogonal to the border. This choice greatly simplifies the analysis and gives a geometrical interpretation for the fixed points of the renormalization group flow. Examples are constructed that present asymptotic freedom, confinement of static quarks, either with vanishing or nonvanishing gluon condensate G2. The latter models require an extension of the dilaton-gravity models already considered in the literature. This extension is also determined by the only input, i.e. the β-function. In addition, the restrictions imposed by the trace anomaly equation (TAE) are studied. In doing so, a holographic derivation of this equation is presented.